Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ejon.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Working in silos? – Head & Neck cancer patients during and after treatment with or without early palliative care referral

Abstract: To avoid H&N cancer care in silos, a closer integration between the oncology and the palliative care team is needed. Further research on the complex situation of having oncological treatment concurrent with palliative care, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Improving coordination and reducing the fragmentation in care, are central parts of the CCN function. We chose to study care coordination in relation to cancer care transitions, since these were reported to be major areas of concern prior to the study (Regional Cancer Center Stockholm-Gotland, 2013;Ullgren et al, 2017). Our results showed statistically significant improvements in care coordination between baseline and follow-up for only one of the six study specific questions (Table 4).…”
Section: Coordination Of Carementioning
confidence: 82%
See 3 more Smart Citations
“…Improving coordination and reducing the fragmentation in care, are central parts of the CCN function. We chose to study care coordination in relation to cancer care transitions, since these were reported to be major areas of concern prior to the study (Regional Cancer Center Stockholm-Gotland, 2013;Ullgren et al, 2017). Our results showed statistically significant improvements in care coordination between baseline and follow-up for only one of the six study specific questions (Table 4).…”
Section: Coordination Of Carementioning
confidence: 82%
“…To evaluate the patients' experience of coordination, we focused on care transitions. The purpose was to try to capture the issues around fragmented care, reported in previous evaluations (Regional Cancer Center Stockholm-Gotland, 2013;Ullgren et al, 2017). We used the items described below from the study specific questionnaire.…”
Section: Coordination Of Carementioning
confidence: 99%
See 2 more Smart Citations
“…A partnership model of care was emphasised as integral by healthcare professionals, representing a more gradual transition from one team to another. This is noteworthy as service issues can arise when integration between teams is lacking for those caring for HNC patients [33]. A broad MDT approach is needed to best optimise care, in particular focusing on information and psycho-social needs.…”
Section: How This Study Relates To Existing Literaturementioning
confidence: 99%